Giles Land—a mystery for S.A. Andrée and other early Arctic explorers - Björn Lantz (Polar Research, 2019)
After the initial discovery of Giles Land (Kvitøya, Svalbard) by Cornelis Giles in 1707, it was most likely never seen by anyone again until 1876. During this lengthy period, Giles Land evolved into an enigma as various explorers and cartographers came to very different conclusions about its probable location, character or even existence. In 1897, when the engineer Salomon August Andrée tried to return over the ice after his failed attempt to reach the North Pole in a balloon, he passed through an area approximately 160 km north of Kvitøya where Giles Land was indicated on his map. Andrée searched for it, but there was no land in sight. The main reason why Giles Land was erroneously positioned too far north was a conjecture by a German cartographer August Petermann in 1872. While there was some distrust of Petermann’s conjecture at the time, many also believed it. The erroneous understanding that Giles Land was located far north of Kvitøya was only finally dismissed in the 1930s. This article examines how this misunderstanding regarding the identity and location of Giles Land could arise and become entrenched.